Measurement of the void fraction of R-134a flowing through a horizontal tube - Srisomba, R.; Mahian, O.; Dalkilic, A. S.; Wongwises, S. (PERGAMON-ELSEVIER SCIENCE LTD, 2014)
This experiment aims to measure the void fraction of R-134a refrigerant flowing through a horizontal tube, using a quick-closing valve and optical observation techniques. The tube is transparent, circular, 115 mm long with an inside 8 mm thick, and has two actuator ball valves installed at both ends. The experiment was conducted in conditions where vapor quality ranged from 1% to 82%, saturated temperature was from 23 to 30 degrees C, and mass flux was from 644 to 1455 kg/m(2) s. The results of the experiment indicate that raising the saturated temperature decreased the void fraction, whereas increasing mass flux had no significant effect on it. Moreover, results also show three flow regimes: intermittent, wavy, and annular. Each. flow regime led to different predicted void fractions. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Two-phase flow; Void fraction; Optical observation technique; Void fraction correlation; Quick closing valve method; INTERFACIAL MEASUREMENTS; STRATIFIED TYPES; PART II; Thermodynamics; Mechanics